2017
DOI: 10.4172/2329-891x.1000246
|View full text |Cite
|
Sign up to set email alerts
|

Performance of GeneXpert Assay in Detecting Pulmonary Tuberculosis and Rifampicin Resistance in Patients Attending Kitui County Hospital, Kenya

Abstract: Background: To combat the challenges of TB epidemic in Kenya there has been massive scale up of both treatment and diagnostic facilities.The challenges encountered in these centers is failure to accurately detect Mycobacterium tuberculosis. In this work, we aimed at evaluating the performance of GeneXpert MTB/RIF assay in detection of pulmonary TB and drug resistant testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
4
7
0
Order By: Relevance
“…In this study, Mycobacterium tuberculosis was prevalent in all ages, but have seriously hit the age group of 30-44 years with 26.0% and of whom 34/420 (8.1%) were rifampicin resistant. The positivity nding was in line with studies conducted in Gondar (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] and Agaro Teaching Health Center in southwestern Ethiopia [36].However, contrary ndings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, Mycobacterium tuberculosis was prevalent in all ages, but have seriously hit the age group of 30-44 years with 26.0% and of whom 34/420 (8.1%) were rifampicin resistant. The positivity nding was in line with studies conducted in Gondar (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] and Agaro Teaching Health Center in southwestern Ethiopia [36].However, contrary ndings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 84%
“…Our nding was similar to studies conducted in the Debre Markos Hospital (23.2%) [13], Gondar Referral Hospital (24.6%) [14], Gambella (20.0%) [46], Afar (24.5%) [49], India (27.6%) [4], South Africa (26%) [15], Nigeria (22.9 %) [16] And the WHO report in Africa (25%) [2]. However, it was lower compared to reports in Jigjiga (65.5%) [17], Kenya (32.25%) [18], in eastern Uttar Pradesh (32.9%) [19] and Congo (79.1%) [47].The main difference in these latter ndings may show our inclusion of all forms of presumptive tuberculosis while other studies included identi ed cases of Mycobacterium tuberculosis. In contrast, our nding was higher when compared with studies conducted in Metema and Armacho (5.7%) [6], Felege Hiwot Referral Hospital, and Debre Tabor Hospital (14.6%) [20], in three referral hospitals and the regional laboratory in Addis Ababa (15.11%) [48], other parts of Ethiopia (4.7%-10.8%) [21][22][23], Nigeria (10.3%) [24] and India (2.31%) [25].The variations might be due to the difference in study design, type and number of participants, and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The positivity finding was in line with studies conducted in Gonder (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] & Agaro Teaching Health Center in southwestern Ethiopia [36]. There are however contrary findings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 81%
“…Our finding was similar to studies conducted in the Debre Markos Hospital (23.2%) [13], Gondar Referral Hospital (24.6%) [14], Gambella (20.0%) [46], Afar (24.5%) [49], India (27.6%) [4], South Africa (26%) [15], Nigeria (22.9 %) [16] And the WHO report in Africa (25%) [2]. However, it was lower compared to reports in Jigjiga (65.5%) [17], Kenya (32.25%) [18], in eastern Uttar Pradesh (32.9%) [19] and Congo (79.1%) [47]. the main difference in these latter findings may show our inclusion of all forms of presumptive tuberculosis while other studies included identified cases of Mycobacterium tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was similar to studies conducted in the Debre Markos Hospital (23.2%) [15], Gondar Referral Hospital (24.6%) [16], Gambella (20.0%) [17], Afar (24.5%) [18], India (27.6%) [4], South Africa (26%) [19], Nigeria (22.9%) [20] And the WHO report in Africa (25%) [2]. However, it was lower compared to reports in Jigjiga (65.5%) [21], Kenya (32.25%) [22], in eastern Uttar Pradesh (32.9%) [23] and Congo (79.1%) [24]. The main difference in these latter findings may show our inclusion of all forms of presumptive tuberculosis while other studies included identified cases of Mycobacterium tuberculosis.…”
Section: Discussionmentioning
confidence: 99%